Web-based unit and instructor evaluation system (UIES) - Choon, Kwai Mui (2005)
The aim of this project is to develop performance evaluation system to achieve TARC business strategy which is to provide quality education and training and maintain high academic standards in all education programs offered in the college. This Web-Based Unit & Instructor Evaluation System (UIES) is an automated system designed to replace the current paper-based evaluation system. By using this web-based system, TARC can conduct unit evaluation via an online system that can lower costs, increase timelines of feedback, and make the record keeping and analysis easier. Literature review was conducted to understand the current state of knowledge and practice within the project topic - Web-based Unit and Instructor Evaluation System. The UIES system was developed based on Object Oriented System Analysis and Design (OOSAD). The framework of the system is based on Apache Web Server + PHP + MySQL.